Answer:
![$\frac 3 4$](https://img.qammunity.org/2023/formulas/mathematics/college/369uqp4wo43j4e5h0jwrpo0m6gn5a4yrj0.png)
Explanation:
We have the following series
![$\sum_(i=1)^(\infty){(1)/(n(n+2)) } = (1)/(1\cdot 3)+(1)/(2\cdot 4)+(1)/(3\cdot 5)+\dots $](https://img.qammunity.org/2023/formulas/mathematics/college/fua0boh45rn97f66usm8zwm36786d3kfd2.png)
From this series, you can note a telescope series, thus
![$\sum_(n=1)^\infty (1)/(n(n+2))=\frac1 2\sum_(n=1)^\infty\left(\frac 1 n-\frac 1{n+2}\right)$](https://img.qammunity.org/2023/formulas/mathematics/college/kpvkvb5n8tw2ste9vn7w7qraflgrfbzld8.png)
Now we just have to calculate the limit as
![n\to\infty](https://img.qammunity.org/2023/formulas/mathematics/high-school/c9bdrpkcrxxgt8tp9z7je8u9xiy9o226kr.png)
For this case we can see that
![$\sum_(n=1)^m\left(\frac1 n-\frac1{n+2}\right)=1+\frac12-\frac1{m+1}-\frac1{m+2}$](https://img.qammunity.org/2023/formulas/mathematics/college/z000hnzfbgzpprujn5n8shzu29zxrayz4c.png)
This is because there is a pattern
![$\left((1)/(1){-(1)/(3)}\right)+\left((1)/(2){-(1)/(4)}\right)+\left((1)/(3)-(1)/(5)\right)+\left((1)/(4)-(1)/(6)\right)+\left((1)/(5)-(1)/(7)\right)+\left((1)/(6)-(1)/(8)\right)+\dots}$](https://img.qammunity.org/2023/formulas/mathematics/college/7s8kam27r65ci3mqbrdvn0u37i5j1nfiqq.png)
in which every fraction from
get cancelled, it implies that we are only left with
![$(1)/(1) +(1)/(2) = 1+(1)/(2) =(3)/(2) $](https://img.qammunity.org/2023/formulas/mathematics/college/g56bvpdq3xms9032r2qwc92nr3p23pf59o.png)
Therefore,
![$\sum_(n=1)^\infty (1)/(n(n+2))=\frac1 2\sum_(n=1)^\infty\left(\frac 1 n-\frac 1{n+2}\right) = \frac1 2 \left(\frac 3 2\right) = \boxed{\frac 3 4}$](https://img.qammunity.org/2023/formulas/mathematics/college/lmgkr25zw9cbbbea2ski5qhnmxbqzl5uh9.png)